Battery Energy Storage System in Peak Shaving Application - Nasir, Nor Najwaton; Hussin, Siti Maherah; Hassan, Mohammad Yusri; Rosmin, Norzanah; Mat Said, Dalila; Md Rasid, Madihah (Applications of Modelling and Simulation, 2018)
The paper discusses the performance of battery energy storage system in peak shaving. The battery energy storage system technologies have a great potential in shifting the electricity demand from on-peak to off-peak period. This technique is very important especially for commercial and industrial sectors since they have to pay to utility company some additional cost of 30% of their peak demand due to the usage of expensive open-cycle gas power plants. Thus, this paper discusses the effectiveness of using lithium-ion battery in reducing the peak demand. This kind of battery is chosen due to its high efficiency in charging and discharging as well as its high energy density. The performance of the proposed battery is analyzed using Matlab/Simulink simulation. The result shows that the lithium-ion battery is very effective in shifting the demand from on-peak to off-peak period.